Syndicats : lendemains de crise ? - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "Syndicats : lendemains de crise ?," by Jean-Marie Pernot.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Human Face of Industrial Conflict in Post-War Japan - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "The Human Face of Industrial Conflict in Post-War Japan," edited by Hirosuke Kawanishi.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

La confiance : approches économiques et sociologiques - Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "La confiance : approches économiques et sociologiques," edited by Christian Thuderoz, Vincent Mangematin and Denis Harrisson.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Trust (Psychology)

The Labour Movement and Civil Society: Reflections on the People's Summit from Quebec - Gagnon, Mona-Josée (Just Labour: A Canadian Journal of Work and Society, 2002)
The legal approach in Canada towards the regulation of trade union democracy has sought to balance individual member's rights with respect for the autonomy of unions. While the United States and England have heavily legislated the areas of internal trade union affairs, Canada has enacted relatively few laws in this area. Rather, unions in Canada have enjoyed considerable legal freedom to develop their own democratic practices and culture. The irony of this approach is that it is the Canadian courts, rather than the more experienced and liberal labour relations boards, that are the final legal arbiters over most internal union matters. However, this is slowly changing. Several provinces have recently enacted modest changes that direct their labour boards to hear complaints from union members respecting the fairness of internal hearings. In the absence of extensive statutory regulation, union constitutions and the democratic traditions behind them become significant legal documents

Les intellectuels critiques et le mouvement ouvrier au Québec: fractures et destin parallèle - Gagnon, Mona-Josée (Cahiers de recherche sociologique, 2000)

Syndicalisme et classe ouvrière. Histoire et évolution d’un malentendu - Gagnon, Mona-Josée (Lien social et Politiques, 2003)
Prenant son départ dans une réflexion sur la notion de classe sociale, cet article analyse l’histoire et l’évolution du syndicalisme eu égard à son lien avec une classe ouvrière qu’il a eu pour mission de représenter. La construction de deux paradigmes contraires, qui se sont succédé et qui font écho à différents changements sociaux, permet de mettre en relief et de sérier les problèmes identitaires qui affectent le syndicalisme, tant dans son rôle de régulation que dans son rôle de contestation. La remise en question de la représentation biclassiste de la société, qui a caractérisé tant la pensée marxiste et le projet social-démocrate que plusieurs courants d’analyse sociologique, jointe à la « disqualification » de la classe ouvrière comme principal acteur du changement social, témoigne de la nécessité de rethéoriser le syndicalisme selon une approche dialectique, seule capable de prendre en compte les contradictions multiples qui façonnent le fait syndical.

Brazilian Trade Unions: In (In)Voluntary Confinement of the Corporatist Past - Lang, Karen; Gagnon, Mona-Josée (Relations industrielles / Industrial Relations, 2009)
Many analysts of Brazilian industrial relations share a determinist vision of the country's trade unionism, according to which the unions maintain a paradoxical yet atavistic relationship with the heavy body of laws that provide them with advantages while limiting their freedom. We tested this vision by conducting field enquiries into the daily activities of two Brazilian unions: the ABC Metalworkers Union and the Seamstress Union for the Sao Paulo and Osasco Region. In this article, we present the results of our case studies and what they reveal about Brazilian trade unionism's relationship with the labour legislation. We also briefly discuss former trade union leader and current President Lula's recent attempts to reform the country's labour relations system.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Unionization

The International Activities Of Trade Unions: A Sociohistorical Analysis Based On The Case Of Quebec - Gagnon, Mona-Josée; Avignon, Pierre; Collombat, Thomas (Studies in Political Economy, 2006)
The countersummit of the Americas, held in Quebec City in April 2001 under the auspices of the Hemispheric Social Alliance (HSA) and in opposition to the creation of the Free Trade Area of the Americas (FTAA), promised to be a prelude to a new phase in how trade unions handle the issue of globalization. There was hope that trade unions would truly take charge of this issue. In terms of political organization, logistics, and the number ofactive participants, Quebec trade union organizations dominated the event....This article addresses two central questions. First, does the mobilization of Quebec trade unions against neoliberal globalization represent a break, both quantitative and qualitative, in their approach to international trade union relations? Second, what does the Quebec example tell us about the sociohistorical dynamics of international trade union relations in the Americas, and even beyond? We have attempted to investigate thoroughly how relations between trade unions have been conducted internationally before and after April 2001. For the most part, this study was undertaken at the end of 2002 and the beginning of 2003, with some updates made in 2004. –From introduction

La FTQ comme acteur politique - Gagnon, Mona-Josée (La FTQ, ses syndicats et la société québécoise, 2001)
OCLC: 48999692
Keywords: 20e siècle; Actes de congrès; Conference papers and proceedings; Fédération des travailleurs du Québec; Fédération des travailleurs du Québec Congresses; Fédération des travailleurs du Québec History Congresses; Fédération des travailleurs et travailleuses du Québec Histoire Congrès; Fédération des travailleurs et travailleuses du Québec. Congrès; Histoire; History; Labor unions; Labor unions Québec (Province) Congresses; Québec; Québec (Province); Syndicalism; Syndicalism Québec (Province) Congresses; Syndicalisme; Syndicalisme Québec (Province) Congrès; Syndicat; Syndicats Québec (Province) Congrès; proceedings (reports)